Family support and diabetic dietary compliance among patients with type 2 diabetes mellitus - Afifah Qonitah Khoirunisa; Elida Soviana (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Controlling blood glucose needs to be done in patients with Diabetes mellitus so that the level is close to the normal threshold. Complications such as retinopathy, neuropathy, and nephropathy can occur as a result of uncontrolled blood glucose levels. To keep their blood glucose levels stable, people with diabetes mellitus can control their diet according to a predetermined diet. Adherence to a diabetes mellitus diet can be influenced by family support Positive family support will generate motivation both when it comes to controlling diet patterns and blood sugar levels Purpose: To determine the relationship between family support and dietary adherence in patients with type 2 diabetes mellitus in the Diabetes Mellitus Association of Surakarta. Method: Observational research with a cross sectional design. This research was carried out at the Diabetes Mellitus Association of Surakarta, with a sample of 41 people. The instruments used in this study were the Hensarling Diabetes Family Support Scale (HDFSS) questionnaire and the Perceived Dietary Adherence Questionnaire (PDAQ) questionnaire Results: The relationship between family support and dietary adherence was found that as many as 28 respondents (93.4%) had a high family support category with high dietary adherence compared to respondents who had a low family support category with low dietary adherence as many as 6 respondents (54.5%). The results of the statistical test on the variable of family support with dietary adherence obtained a value of p = 0.008 (p <0.05) which means that there is a relationship between family support and dietary adherence in patients with type 2 diabetes mellitus in the Diabetes Mellitus Association of Surakarta Conclusion: There is a relationship between family support and dietary compliance in type 2 diabetes mellitus patients at the Surakarta Diabetes Mellitus Association.